Pharmacokinetic-Pharmacodynamic Characterization of Relapse Risk for Paliperidone Palmitate 1-Month and 3-Month Formulations. Issue 6 (November 2019) - Russu, Alberto; Savitz, Adam; Mathews, Maju; Gopal, Srihari; Feng, Yu; Samtani, Mahesh N.
Abstract: Background: Pharmacokinetic-pharmacodynamic (PK/PD) models were developed to describe the relationship between the time course of paliperidone plasma concentrations and the risk of relapse of schizophrenia symptoms following administration of paliperidone palmitate 1-month (PP1M) and 3-month (PP3M) long-acting injectables, and to identify relevant covariates for relapse and dropout events. Methods: Patient data from two global phase 3, relapse prevention studies comparing PP3M to placebo (study A) and PP3M to PP1M (study B) were analyzed. Dropout and relapse data were assessed using survival analysis as two separate single time-to-event models. Baseline covariates included age, sex, race/country, duration of illness, previous hospitalizations, prior use of long-acting injectables and use of multiple (≥2) antipsychotics at screening. Results: The PK/PD analysis data set included 305 patients who were randomized to receive PP3M or placebo in the double-blind phase of study A and 1002 patients randomized to receive PP3M or PP1M in the double-blind phase of study B. Risk of relapse decreased with increasing paliperidone concentrations for both PP1M and PP3M, while it appeared to increase in patients with higher number of previous hospitalizations and/or with higher prerandomization (trough) paliperidone concentration (study A), and in patients on concomitant benzodiazepine medication and/or at Japan centers (study B). These findings are reflective of different illness severity in the population and of differences in medical practice for Japanese patients. In model-based simulations, PP3M and PP1M displayed similar relapse rates over time. Conclusions: This PK/PD analysis confirmed that PP1M and PP3M provide comparable efficacy in terms of relapse prevention, and that PP3M is superior to placebo. The PK/PD models presented here may as well be applied to studies with similar designs as either study A or B. Abstract : Supplemental digital content is available in the text.